The craft of ritual studies - Grimes, Ronald L. (Oxford University Press, 2014)
"In religious studies, theory and method research has long been embroiled in a polarized debate over scientific versus theological perspectives. Ronald L. Grimes shows that this debate has stagnated, due in part to a manner of theorizing too far removed from the study of actual religious practices. A worthwhile theory, according to Grimes, must be practice-oriented, and practices are most effectively studied by field research methods. The Craft of Ritual Studies melds together a systematic theory and method capable of underwriting the cross-cultural, interdisciplinary study of ritual enactments. Grimes first exposes the limitations that disable many theories of ritual--for example, defining ritual as essentially religious, assuming that ritual's only function is to generate group solidarity, or treating ritual as a mirror of the status quo. He proposes strategies and offers guidelines for conducting field research on the public performance of rites, providing a guide for fieldwork on complex ritual enactments, particularly those characterized by social conflict or cultural creativity. The volume also provides a section on case study, focusing on a single complex event: the Santa Fe Fiesta, a New Mexico celebration marked by protracted ethnic conflict and ongoing dramatic creativity. Grimes explains how rites interact creatively and critically with their social surroundings, developing such themes as the relation of ritual to media, theater, and film, the dynamics of ritual creativity, the negotiation of ritual criticism, and the impact of ritual on cultural and physical environments. This important and influential book will be the capstone work of Grimes's three decades of leadership in the field of ritual studies. It is accompanied by twenty online appendices illustrating key aspects of ritual study"--